DIGITAL DEVELOPMENT OF DIVIDEND POLICY IN JOINT-STOCK COMPANIES IN THE REPUBLIC OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
It is known that the dividend policy is an integral part of the decisions of the company's management in the field of financing. The most important aspect of the company's dividend policy is to find the optimal ratio of profit distribution between dividend payments and that part of it that remains within the company for its development.